The SARS-CoV-2 Omicron BA.1 spike G446S mutation potentiates antiviral T-cell recognition - Motozono, Chihiro; Toyoda, Mako; Tan, Toong Seng; Hamana, Hiroshi; Goto, Yoshihiko; Aritsu, Yoshiki; Miyashita, Yusuke; Oshiumi, Hiroyuki; Nakamura, Kimitoshi; Okada, Seiji; Udaka, Keiko; Kitamatsu, Mizuki; et al. (Nature communications, 2022)
Although the Omicron variant of the SARS-CoV-2 virus shows resistance to neutralizing antibody, it retains susceptibility to the cellular immune response. Here we characterize vaccine-induced T cells specific for various SARS-CoV-2 variants and identified HLA-A*24:02-restricted CD8 + T cells that strongly suppress Omicron BA.1 replication in vitro. Mutagenesis analyses revealed that a G446S mutation, located just outside the N-terminus of the cognate epitope, augmented TCR recognition of this variant. In contrast, no enhanced suppression of replication is observed against cells infected with the prototype, Omicron BA.2, and Delta variants that express G446. The enhancing effect of the G446S mutation is lost when target cells are treated with inhibitors of tripeptidyl peptidase II, a protein that mediates antigen processing. These ex vivo analysis and in vitro results demonstrate that the G446S mutation in the Omicron BA.1 variant affects antigen processing/presentation and potentiates antiviral activity by vaccine-induced T cells, leading to enhanced T cell recognition towards emerging variants. Mutations in the spike of SARS-CoV-2 can result in the escape of the neutralising antibody response but may retain susceptibility to the cellular immune response. Here the authors show the G446S mutation in the spike protein of Omicron BA.1 is associated with altered antigen presentation and potentiates activation of specific T cell immunity.